2005
DOI: 10.1037/0278-7393.31.5.891
|View full text |Cite
|
Sign up to set email alerts
|

Constituent Structure and Linear Order in Language Production: Evidence From Subject-Verb Agreement.

Abstract: A number of studies have shown that structural factors play a much larger role than the linear order of words during the production of grammatical agreement. These findings have been used as evidence for a stage in the production process at which hierarchical relations between constituents have been established (a necessary precursor to agreement), but before the final linear order of words is determined. The current article combines evidence from off-line ratings, online production studies, and a corpus analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 36 publications
4
67
1
1
Order By: Relevance
“…Franck et al (2002) found that when the subject phrase contained two stacked PP modifiers like ''The inscription(s) on the door(s) of the toilet(s)" the medial prepositional phrase led to more attraction errors than the most deeply embedded one. These results suggest that structural distance between a potential attractor and the subject head noun, or its syntactic projection, impacts the likelihood of attraction more so than its linear distance to the verb (although see Haskell & MacDonald, 2005, for arguments that small but measurable linear distance effects also exist).…”
Section: Productionmentioning
confidence: 90%
See 1 more Smart Citation
“…Franck et al (2002) found that when the subject phrase contained two stacked PP modifiers like ''The inscription(s) on the door(s) of the toilet(s)" the medial prepositional phrase led to more attraction errors than the most deeply embedded one. These results suggest that structural distance between a potential attractor and the subject head noun, or its syntactic projection, impacts the likelihood of attraction more so than its linear distance to the verb (although see Haskell & MacDonald, 2005, for arguments that small but measurable linear distance effects also exist).…”
Section: Productionmentioning
confidence: 90%
“…These factors include the number features on potential attractors, their relative structural depth with respect to the grammatical controller, and linear order. (Bock & Cutting, 1992;Bock & Eberhard, 1993;Bock & Miller, 1991;Hartsuiker, Antón-Méndez, & Van Zee, 2001;Haskell & MacDonald, 2005; Thornton & MacDonald, 2003;Vigliocco and Nicol, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Already some of the earliest descriptions of attraction errors in the linguistic literature noted an effect of linear distance between agreement controller and an interpolated noun on the likelihood of attraction errors, and consequently dubbed the effect 'proximity concord' (Hale & Buck, 1903/1966, cited after Francis, 1986Quirk, Greenbaum, & Leech, 1989). For structures with a single prepositional phrase modifier used here and in many earlier studies, linear precedence between candidate noun phrases seems to play a major role in the explanation of attraction effects during on-line processing (Fayol et al, 1994; also see Haskell & MacDonald, 2005). …”
Section: Agreement and Agreement Errorsmentioning
confidence: 99%
“…Haskell and MacDonald 2005, Franck et al 2002, 2006, Benmamoun and Lorimor 2006). Thus agreement takes place in two steps: first in the syntax and then in the PF.…”
mentioning
confidence: 99%